HADITH AND THE ETHICS OF PUBLIC SPACE: the Case of the Sea Fence Conflict in Tangerang - Ilman Hendrawan Saputra (Riwayah: Jurnal Studi Hadis, 2025)
The construction of a sea fence on the coast of Tangerang Regency has raised multidimensional issues that include aspects of agrarian law, socio-economic impacts, and violations of Islamic law principles. This study aims to examine the legality of the sea fence project and its implications for coastal communities through the perspective of the hadith of the Prophet Muhammad and to assess its compatibility with Indonesian legislation. Using a multidisciplinary approach, the research employed coastal abrasion data based on historical Google Earth imagery (1985-2024), linear regression modeling for past shoreline estimation, analysis of agrarian regulations such as PP No. 24 of 1997 and Permen ATR/BPN No. 17 of 2021, as well as the study of relevant sahih hadiths. Results show that the project triggers administrative irregularities through falsification of land documents and abuse of authority, which not only violates positive law but also contradicts the hadith “Whoever cheats is not from my group” (HR Muslim No. 102), as well as the threat to leaders who are not trustworthy (HR Bukhari No. 7150). Another hadith even asserts that land grabbers will be drowned in seven layers of earth on the Day of Judgment (HR. Bukhari No. 2454). The social impacts include loss of sea access for fishermen, economic losses, and horizontal conflicts. This research recommends strict selection of land officials, training on land-related laws, and field-based document verification to realize fair governance of public space.